Modelling the Effect of Time Overrun and Inflation Rate on Completion Cost of Construction Projects in Nigeria - Diugwu, Ikechukwu A.; Etuk, Ette H.; Baba, Dorothy L.; Mohammed, Musa; Yakubu, Henry A. (International Journal of Sustainable Construction Engineering and Technology, 2017)
Variations in approved cost of projects are common and could be triggered by a fluctuation in interest rates and variation project duration. The paper aimed to explain the effect of time overrun (TO) and inflation rate on project completion cost (PCO). Variations in costs and durations of projects were calculated for 250 government and private building projects executed between 2005 and 2015, while inflation rates for the last quarter of these years were used. A multiple regression analysis of cost overrun as the endogenous variable, with time overrun and inflation rates as the exogenous variable was conducted for private and government funded projects. The result revealed that the cost overrun can be predicted by the equations; predicted private cost overrun = -669673.60 + 50182.35 (time overrun) + 106690.20 (inflation rate), and predicted government cost overrun = -9805996 – 148721.90 (time overrun) + 1266038 (inflation rate) respectively for private and government funded projects. Also, while there is an evidence of significant relationship between completion cost of projects and variations in time and inflation rate for both private and government funded projects, the mean variations between time overrun and inflation rate viz-a-viz completion cost are not equal for private and government funded projects.